Klein-Gordon-Fock equation from Einstein general relativity - Thuan, Vo Van (Communications in Physics, 2016)
A time-space symmetry based cylindrical model of geometrical dynamics was proposed. Accordingly, the solution of Einstein gravitational equation in vacuum has a duality: an exponential solution and a wave-like one.  The former leads to a "microscopic" cosmological model with Hubble expansion. Due to interaction of a Higgs-like cosmological potential, the original time-space symmetry is spontaneously broken, inducing a strong time-like curvature and a weak space-like deviation curve.  In the result, the wave-like solution leads  to Klein-Gordon-Fock equation which would serve  an explicit approach to the problem of consistency between quantum mechanics and general relativity.